Implementasi Program Penanganan Kawasan Permukiman Kumuh Di Kabupaten Malang - Syafiqotul Maulah, Nur; Manggalou, Singgih (Jurnal Administrasi Politik dan Sosial, 2024)
This research aims to determine the implementation of the program for handling slum areas in Malang Regency, based on seven criteria in PUPR Ministerial Regulation No.14/PRT/M/2018, namely building conditions, environmental roads, drinking water supply, environmental drainage, waste water management, waste management, and fire protection. Using qualitative case study methods, data was obtained through interviews, literature study and documentation. The research results show that this program has succeeded in reducing slum areas by 64.83% from a total of 3,223.29 hectares, with the remaining 1,133.76 hectares still needing to be addressed. The strategies implemented include infrastructure development, community empowerment, and collaboration between the government, private sector and society. The implementation of this program has had a significant impact on reducing slum areas and improving the quality of life of the community. Sustainability of environmentally based policies and approaches is needed to comprehensively resolve the remaining challenges and create livable settlements.